Malaysian Crude Oil Emulsions : Stability Study - B. Pramudono; H. B. Mat (Dept. of Chemical Engineering, Diponegoro University, 2002)
The stability of water-in-oil emulsion of some Malaysian crude oils was studied with particular emphasis on effect of interfacial active components existed in the crude oil, i.e. asphaltene, resin and wax. The emulsion stability was studied by measuring the volume of water or oil phase separated in variation with time, water hold up, and the heights of the sedimenting/coalescing interfaces during the separation at various temperatures. The study investigated the influence of asphaltene, resin and wax on emultion stability if it`s present in the crude oil alone, together or combination one of the others. The result show that the interfacial active component that stabilize emulsion is asphaltene. The resin and wax do not form stale emulsion either aloneor together. There is a correlation between emulsion stability and physicochemical properties of crude oil which showed that higher asphaltene content in the crude oil would form more stable emultion. Increased temperature was found to cause instability of emultion. Keywords : emultion stability, crude oil, asphaltene, resin and wax